PENGGUNAAN WORDWALL TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Riyadi Saputra; Wiwik Okta Susilawati; Sandra Febriyaningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this study is the low student motivation and learning outcomes due tothe lack of variation in media used during the learning process. This study aims todetermine the effect of using the interactive learning media Wordwall on students' learningoutcomes in the subject of Natural and Social Sciences (IPAS) for Grade IV at SDN 02Koto Salak. Wordwall, as an interactive digital media, is considered capable of creatingan engaging and enjoyable learning atmosphere for students.The method used in this studyis quantitative with a quasi-experimental design. The research sample consisted of twoclasses: the experimental class, which used Wordwall, and the control class, which usedconventional methods. Data were obtained through pre-tests and post-tests to measureimprovements in learning outcomes. Data analysis using the t-test showed a significantdifference between the experimental and control classes. The results of the study provedthat the use of Wordwall had a positive effect on students' learning outcomes.